2019
DOI: 10.3390/environments6080087
|View full text |Cite
|
Sign up to set email alerts
|

Paving the Way for A Sustainable and Efficient SiO2/TiO2 Photocatalytic Composite

Abstract: Although photocatalysis is an extraordinary and tremendously explored topic, there is a need to find new ways to encourage the production of composite materials that are economical, efficient and with limited environmental impact. Nanocatalysts may benefit from appropriate support material for many reasons. In this study, TiO2 was deposited on SiO2, so that the silica not only provides the macroscopic structure on which the TiO2 is formed, but it positively affects the photocatalytic activity as well. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…The second best photocatalyst TiO2/Dt(13%) is composed of the highest loading TiO2 (39% anatase and 61% rutile). This result in agreement with previous research works in which it is reported that when the wt.% of SiO2 added to TiO2 ranged from 5 to 20 wt.%, the mixed oxide TiO2/SiO2 exhibited a higher photocatalytic efficiency compared to pure nano-TiO2 prepared with different Ti and Si precursor [36,44,69,70]. Concerning the composite TiD(29%) with 63% of anatase, the photodegradation rate of MDMA is less important compared to TiD(34%) which contains 90 wt.% of anatase due to its low value of bad gap (2.89 eV) and strong absorption above 400 nm.…”
Section: Effect Of Saa On Adsorption/photodegradationsupporting
confidence: 93%
“…The second best photocatalyst TiO2/Dt(13%) is composed of the highest loading TiO2 (39% anatase and 61% rutile). This result in agreement with previous research works in which it is reported that when the wt.% of SiO2 added to TiO2 ranged from 5 to 20 wt.%, the mixed oxide TiO2/SiO2 exhibited a higher photocatalytic efficiency compared to pure nano-TiO2 prepared with different Ti and Si precursor [36,44,69,70]. Concerning the composite TiD(29%) with 63% of anatase, the photodegradation rate of MDMA is less important compared to TiD(34%) which contains 90 wt.% of anatase due to its low value of bad gap (2.89 eV) and strong absorption above 400 nm.…”
Section: Effect Of Saa On Adsorption/photodegradationsupporting
confidence: 93%
“…Whereas the ratio between the produced NO 2 and the removed NO is constant and around 16% for reference, zeolite, and activated carbon specimens, it is significantly lower when silica gel is used. This synergistic effect was already found in previous studies (Pierpaoli et al, , 2019b and may be attributed to an enhanced reactivity with the Ti-OH via NO 2 disproportion (Eq. 9) caused by a more available adsorbed water in the vicinity of the photocatalyst (Dalton et al, 2002) and by the subsequent reaction of the nitrates with alkali or alkaline earth metals ions (Eq.…”
Section: Photocatalytic Oxidationsupporting
confidence: 79%
“…In mortars, the effectiveness of adsorbent aggregates to remove VOCs can reach 65%, as it has been previously tested (Tittarelli et al, 2015;Giosuè et al, 2019b). Adsorbent fillers/aggregates have been also tested to remove NO x in cementitious systems with photocatalytic agents under UV-A radiation (Horgnies et al, 2012;Pierpaoli et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have focused on creating a new class of nano-admixtures in cement-based composites. In this regard, the combination of nano-silica and TiO 2 particles has been tried in order to synergistically derive the beneficial properties of both of them when included in cement-based composites [229,257,258]. Extensive research activities are demanded in these directions with economically viable materials.…”
Section: Issues and Limitationsmentioning
confidence: 99%